?MIXED-LIGAND COMPLEXES OF ZIRCONIUM (IV) AND URANIUM (VI) WITH SALICYLALDEHYDE AND SOME HETEROCYCLIC AZOPYRAZOLONES - AMRALLAII , A.H. (Biological Sciences - PJSIR, 2022)
Mixed-ligand complexes of Zr (IV) and U(VI) with salicylaldehyde (SA) and some heterocyclic azopyrazoloncs (HAP)have been studicdspcctrophotomeuically. All Connedchelates haveratio 1:1:1.The stiochiornctry and thesta- bilityofthebinaryandmixed chelateshavebeenevaluated. Elementalanalysis,molarconductance andIRspectrahave been used for identification of the solid mixed complexes.